Policy Network in Implementing the City Without Slums (Kotaku) Program in Cimahi City - Rizky Ilhami (SEAN Institute, 2023)
Cimahi City, as one of the cities included in the Greater Bandung metropolitan area, faces complex challenges related to slum problems and rapid urbanization. To overcome this problem, the Cimahi City Government launched the City Without Slums (Kotaku) program which aims to create a livable and sustainable urban environment. This research aims to analyze and understand the policy network involved in implementing the Kotaku program in Cimahi City. The research method used is qualitative with a descriptive approach. The research results show that in research related to the implementation of the City Without Slums (Kotaku) program in Cimahi City, it was found that the success of the program really depends on effective collaboration between various actors, including the Central Government, Regional Government and the Business World. In addition, it was found that a well-organized bureaucratic structure and an adequate level of institutionalization were also key factors in supporting the success of the program. Rules of the game consistently followed by actors and judicious use of power also help create a productive work environment. By utilizing policy networks as a strategy for interdependence, related actors are able to achieve common goals and improve the quality of the urban environment and community welfare in Cimahi City.